PENYEDERHANAAN PARTAI POLITIK DALAM SISTEM PEMERINTAHAN PRESIDENSIIL YANG MULTI PARTAI - Kuswanto - (Yuridika, 2013)
Indonesia is a democratic constitutional state that guarantees freedom of association/assembly and freedom of expression under its constitution. The freedom of association is the basic concept of the urge of political parties. Political parties play significant role in the democracy due to the fact that it is the only means of political recruitment. Political parties recruit candidates to poss an office as representatives both in central and local governmental levels. Not only representatives in Indonesia election is also held to appoint executive officials. As Indonesia is presidentialism state with high plurality, it is not easy for the state to have simple electoral system eventhough multiparty put consequences in inefficiency and ineffectivity. However, limiting the number of electoral participant might be in contrast with protection of freedom of assembly. This article examines and concludes that simplifying member of electoral party in the electoral system trough parliamentary threshold in Indonesia is not against human rights protection according to Pancasila and the Constitution of the Republik of Indonesia in Indonesia.